2013
DOI: 10.1038/srep01919
|View full text |Cite
|
Sign up to set email alerts
|

Rice husks as a sustainable source of nanostructured silicon for high performance Li-ion battery anodes

Abstract: The recovery of useful materials from earth-abundant substances is of strategic importance for industrial processes. Despite the fact that Si is the second most abundant element in the Earth's crust, processes to form Si nanomaterials is usually complex, costly and energy-intensive. Here we show that pure Si nanoparticles (SiNPs) can be derived directly from rice husks (RHs), an abundant agricultural byproduct produced at a rate of 1.2 × 108 tons/year, with a conversion yield as high as 5% by mass. And owing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
331
2
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 455 publications
(370 citation statements)
references
References 46 publications
14
331
2
9
Order By: Relevance
“…The CV profiles of Si/GS/C-S@Gr show an activation process over the first few cycles, as indicated by an increase in the CV peak intensity due to kinetic enhancement in the electrode. 45,46 Cathodic CV peaks due to lithiation of both Si and graphite developed at around 0.15 V, with humps at around 0.1 and 0.2 V, for Si/GS/C-S@Gr, whereas they appeared at around 0.17 V in the weight-averaged CV profiles. Distinct anodic CV peaks due to delithiation of Li x Si 15 developed at 0.50 V for Si/GS/C-S@Gr, whereas the corresponding peaks appeared at around 0.53 V in the weight-averaged CV profile and in the CV profile of Si/GS/C-S.…”
Section: Resultsmentioning
confidence: 99%
“…The CV profiles of Si/GS/C-S@Gr show an activation process over the first few cycles, as indicated by an increase in the CV peak intensity due to kinetic enhancement in the electrode. 45,46 Cathodic CV peaks due to lithiation of both Si and graphite developed at around 0.15 V, with humps at around 0.1 and 0.2 V, for Si/GS/C-S@Gr, whereas they appeared at around 0.17 V in the weight-averaged CV profiles. Distinct anodic CV peaks due to delithiation of Li x Si 15 developed at 0.50 V for Si/GS/C-S@Gr, whereas the corresponding peaks appeared at around 0.53 V in the weight-averaged CV profile and in the CV profile of Si/GS/C-S.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Si is a particularly attractive anode material, owing to its high specific capacity of B4,200 mAh g À 1 , excellent material abundance and well-developed industrial infrastructure for manufacturing 16,18 . In the past several years, there has been exciting progress in addressing the issues associated with large volume change (4300%) during lithium insertion and extraction by designing nanostructured Si including nanowires and coreshell nanowires [19][20][21][22] , hollow particles and tubes [23][24][25] , porous materials 26,27 , Si/C nanocomposites [28][29][30] and by using novel binders [31][32][33][34] . One of the remaining issues for Si anodes is the large capacity loss in the first cycle.…”
mentioning
confidence: 99%
“…Cui's group prepared pure silica directly from rice husks and converted these silica particles to SiNPs with a conversion yield as high as 5% by mass (Figure 3a and 3b). 64 It was found that these recovered SiNPs exhibit high performances as LIB anodes, with high reversible capacity (2,790 mAh g -1 ) and long cycle life (86% capacity retention over 300 cycles). Similarly to Cui's report, Jung et al also employed rice husks as the precursor via the same process to prepare silicon-based anodes.…”
Section: Natural Plantsmentioning
confidence: 98%
“…62 As a result, silica derivation from natural resources, especially from rice husks, is much more sustainable and lower cost than alternative methods, and also is attracting considerable research attention. [63][64][65][66] Recently, many researchers employed natural sources as the silica precursors, and then converted such kinds of nature-derived silica to silicon for energy storage applications. Cui's group prepared pure silica directly from rice husks and converted these silica particles to SiNPs with a conversion yield as high as 5% by mass (Figure 3a and 3b).…”
Section: Natural Plantsmentioning
confidence: 99%